The Land Was Theirs : Jewish Farmers in the Garden State - Dubrovsky, Gertrude W. (Book collections on Project MUSE., 2014)
Challenging prevalent stereotypes, Dubrovsky reveals a unique aspect of Jewish life in America. Although Jews have long been stereotyped as urban businesspeople and professionals, they have been successful agriculturalists since biblical times. In their more recent Eastern European history, 96 percent were forced to live in a region known as the Pale of Settlement, where they were forbidden to own land and were restricted to certain occupations. The pernicious rumor that Jews would not work the soil was then widely broadcast. At the end of the 19th century, young Russian intellectuals were det.